Modified simple decompression in the treatment of cubital tunnel syndrome: avoiding ulnar nerve subluxation - Marcus André Acioly; Amanda Mendes Soares; Mariana Lopes de Almeida; Renata Barbosa; Egon Daxbacher; Carlos Henrique Carvalho (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective In this study, we propose a modification to the simple decompression technique that contains the ulnar nerve in the cubital fossa, thus preventing subluxation during forearm flexion movements. Methods Five consecutive patients with leprosy-associated cubital tunnel syndrome underwent surgery with the modified technique between July 2011 and October 2012. Results The most common symptoms were neuropathic pain and sensory changes (both 60%). On the McGowan scale, three patients maintained their preoperative score and two patients improved by two points, while on the Louisiana State University Health Sciences Center scale, two patients maintained the same scores, two improved by two points, and one improved by one point. Four patients were able to discontinue corticosteroid use. The mean follow-up time was 25.6 months (range 2-48 months). There were no recurrences or subluxations in the long-term. Conclusion This alternative technique resulted in excellent functional results, as well as successful withdrawal from corticosteroids. Furthermore, it resulted in no ulnar nerve subluxations.